A influência do Estágio Profissional no desenvolvimento de um futuro professor de Educação Física - João Mateus Santos (2022)
This document arises from the Professional Internship inserted in the second cycle in Physical Education Teaching of Elementary and Secondary Education of the Sports College of the Oporto University. It is the report of the work of a Physical Education intern teacher throughout the year of the Professional Internship in the Secondary School "António Nobre". This was the ideal time to put in practice everything he learned in his formation with the purpose to evolve himself professionally. This Internship Report was elaborated in order to describe the evolution of the intern student and for that his reflective approach along the process was essential. Every topic developed throughout the document was compared with the literature together with the daily reflections of the intern-student, so that everything was connected with a coherent logic. In this specific case the intern-student had the privilege to experience many different situations that allowed him to evolve a lot by the constant adaptations he needed to perform towards the teaching contexts he was in. His super visioned teaching practice was implemented in a vocational educational class, in which he taught one practical subject and another theoretic, in a regular secondary education class and also in a basic education class. Finally, this document also has a research component, in which a study was carried out with the purpose to encourage students to practice physical exercise through functional training classes in the Physical Education subject. The Professional Internship was definitely a very challenging stage, it allowed the intern-student to evolve greatly and he had the privilege to be accompanied by professionals that oriented him and gave him the fundamental knowledge to practise his teaching profession.